The National Culture as a Determinant of Governance Efficiency: An Empirical Study on Country Level - Anis, Marwa; Hashem, Hana Amr; Heshmat, Dalia Monir; AlSamahey, Mohamed Gamal; Mostafa, Haneen Fathy; Mohamed, Nadeen Tawfik; Lewaa, Israa (The Arab Journal of Administration, 2024)
The present study examines the impact of the national culture on the country-level governance efficiency index. The dimensions of culture as an independent variable is measured using three different cultural frameworks: Hofstede, Globe and Trompenaar. Based on a secondary data collection, the governance efficiency is the dependent variable adopted in the analysis. As the current study is examining whether the national culture has an impact on the governance efficiency index, it is an attempt to understand the determinants of governance. An empirical study was conducted on data involving 177 different countries with different level of incomes. The analysis adopted is the linear regression to test the relationship between the independent and dependent variables and the machine learning models to classify data based on models which have been developed, the other purpose is to find out the best model for predicting the future outcomes. The paper at the end concluded with a discussion of some of the theoretical and practical implications from the results of the empirical study of governance in a number of different countries. It brings a valuable insight into a previously undocumented area of research stressing on the importance of national culture as an important factor and determinant for a better country-level governance.